Sabai Grass Marketing:The Prime Need for Rural Innovation and Economic Development of Tribal Community in the Mayurbhanj District of Orissa State - Satpathy, Asit Ranjan; Sahu, Upendra Nath (Indian Journal of Marketing, 2011)
In a country like India, about 80 percent of the population is living in rural areas and around 70 percent of the population is dependent upon agriculture and allied sectors. The need for rural industrialization is absolutely necessary. About 50 percent of the industrial production of India is accounted for by this sector which also contributes substantially to the country’s exports. Mayurbhanj is also said to be a land of tribals. The tribal community population of the district constitutes about 60 percent of its total population. Out of the 62 tribal communities of Orissa, 45 communities are found in Mayurbhanj alone. This definition of rural marketing rests on the following core concepts: Needs, Wants, And Demands; Products; Utility, Value, And Satisfaction, Exchange, Transactions, And Relationships; Markets; And Marketing And Marketers. The rural marketing of Sabai Grass in Mayurbhanj district is analyzed with the following points taken into consideration-The Method of Marketing, Types of Market Places, setting up Sabai grass enterprise, Marketing Agencies, Cooperative Societies, Market Yard Brokers, Price, Fixation of Price, Distress Sale, Problems of Marketing, Transportation, Storage, Supply of Agricultural Inputs, Marketing Information and Role of Government in agricultural marketing.